EVOLUTION OF THE OCEANIC SULFUR CYCLE AT THE END OF THE PALEOPROTEROZOIC - Johnston D.T.; Wing B.A.; Farquhar J.; Poulton S.W.; Fralick P.W.; Canfield D.E. (My University, 2006)
Here, we present new measurements of 32S, 33S, 34S, and 36S in sedimentary sulfides and couple these measurements with modeling treatments to study the sulfur cycle of a late Paleoproterozoic marine basin. We target the transition in ocean chemistry from the deposition of Paleoproterozoic iron formations (Gunflint Formation, Biwabik Formation, Trommald Formation, and Mahnomen iron formations) to the inferred sulfidic ocean conditions recorded by overlying shale (Rove Formation). The data suggest that certain features of the global sulfur cycle, such as a control by sulfate reducing prokaryotes, and low (mM) concentrations of oceanic sulfate, were maintained across this transition. This suggests that the transition was associated with changes in the structure of the basin-scale sulfur cycle during deposition of these sediments. Sulfide data from the iron formations are interpreted to reflect sedimentary sulfides formed from microbial reduction of pore-water sulfate that was supplied through steady-state exchange with an overlying oceanic sulfate reservoir. The sulfide data for the euxinic Rove Formation shales reflect the operation of a sulfur cycle that included the loss of sulfide by a Rayleigh-like process. We suggest that the prevalence of large and variable heavy isotope enrichments observed in Rove Formation sulfide minerals reflect a sustained and significant net loss of sulfide from the euxinic water column, either as a result of a shallow chemocline and degassing to the atmosphere or as a result of a water column pyrite sink. The inclusion of 36S measurements (in addition to 32S, 33S, and 34S) illustrates the mass-dependent character of these sedimentary environments, ruling out contributions from the weathering of Archean sulfides and pointing to at least modest levels of sustained atmospheric oxygen (>10-5 present atmospheric levels of O2). © 2006 Elsevier Inc. All rights reserved.
Keywords: Archean; Paleoproterozoic; Precambrian::Archean; Докембрий::Архей; Precambrian::Proterozoic::Paleoproterozoic; Докембрий::Протерозой::Палеопротерозойская